TINDAK TUTUR DIREKTIF DALAM DRAMA MIMAN KEISATSU - Siti Umimaya; Hermandra Hermandra; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses directive speech acts. The purpose of this study is to explain directive speech acts in Japanese dramas. The data is directive speech taken from the drama Miman Keisatsu. This research is a qualitative descriptive study. The results of the analysis of Namatame, it was found that directive speech acts were classified into orders (Meirei), requests (irai), prohibitions (kinshi), permission (kyoka) and suggestions (Teian).Key Words: Speech Act, Directive Speech Act, Response